Pengaruh Pola Asuh Orang Tua Terhadap Motivasi Belajar Siswa SMA METHODIST-2 MEDAN - Felix Amanda Marcelino Sitompul; Christine Natania Hutabarat; Hezekiel Rizki Tambunan; Viviansjah Viviansjah; Achmad Irvan Dwi Putra; Beby Astri Tarigan (Universitas Muhammadiyah Metro, 2026)
Learning motivation is an essential determinant of students’ academic achievement and is strongly influenced by the family environment, particularly parenting styles. This study aimed to examine the influence of parenting styles on the learning motivation of eleventh-grade students at SMA Methodist-2 Medan. A quantitative research approach was employed involving 215 students selected from a population of 525 students using proportionate stratified random sampling. Data were analyzed using multiple linear regression analysis after fulfilling statistical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicated that parenting styles had a significant effect on students’ learning motivation, as evidenced by an F value of 9.798 with a significance level of p = 0.000 (p < 0.05). The findings further revealed that parenting styles contributed 10.4% to students’ learning motivation, as reflected in the Adjusted R Square value of 0.104, while the remaining 89.6% was influenced by other variables outside the scope of this study. Partial analysis showed that democratic parenting had a positive and significant effect on learning motivation (p = 0.027), authoritarian parenting also demonstrated a positive and significant effect (p = 0.022), and permissive parenting had the strongest positive influence (p = 0.011). These findings indicate that each parenting style may contribute differently to students’ learning motivation when applied in supportive family contexts. The study highlights the importance of parental involvement, emotional support, and balanced communication in fostering students’ motivation to learn. Practically, the results provide valuable insights for parents and schools in developing strategies to strengthen students’ academic motivation and engagement.